Ontological security dynamics in the EU accession process of North Macedonia - Jekić Aleksandar (Journal of Regional Security)
Ontological security studies emphasize the importance of routinized relations with others. European Integration is understood as a driver of such routinized relations, making it a source of ontological security and the EU an ontological security provider. Yet, as the case of North Macedonia illustrates, the process of EU accession goes along with bilateral disputes and can trigger concerns about ontological (in)security. To fully understand the dynamics of ontological security-seeking and -provision in the EU, the article investigates its limitations in the context of enlargement. This is done through a qualitative analysis of public statements of Macedonian representatives in the period between the Bulgarian veto in 2020 and the French proposal in 2022. Results indicate that the EU's role as a provider of ontological security in the Macedonian case highly depends on the perceived credibility of EU membership, as the latter is seen as a means to gain external recognition and thereby ensure the maintenance of a coherent sense of the Self. Perceptions of low membership credibility, however, challenge the ability of maintaining a coherent sense of the Self and turn the EU into a depriver of ontological security.